Design of an Adaptive Family Communication Model for Parenting in the Digital Era: Integrating FCP and Baumrind's Theory in Indonesian Families - Shafira Angelita Setiya Putri; Maulana Rezi Ramadhana (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The development of digital technology has changed communication patterns within families, particularly interactions between parents and adolescents. High internet access has encouraged a shift from face-to-face communication to digital-based communication, which is shorter and more informal, thus potentially affecting the depth of emotional relationships within families. This situation requires families to adjust so that communication and parenting patterns continue to function effectively in supporting adolescent development. Family communication patterns and parenting styles are two interrelated aspects that shape the quality of emotional relationships, psychosocial development, and the adaptability of adolescents in the digital age. This study aims to formulate a model of parenting communication patterns in families that are adaptive to the development of digital technology. The research uses a qualitative approach with a phenomenological method. Data collection was conducted through in-depth interviews with 15 parents and adolescents at SMAIT Bina Bangsa Sejahtera. he results of the study indicate that family communication patterns play an important role in determining parenting styles in facing the challenges of digital technology. Open and dialogical communication patterns encourage the application of authoritative parenting styles, while closed and permissive communication patterns tend to weaken the quality of relationships and supervision of technology use. This study formulates six main patterns in the adaptive family communication model in the digital era, namely dialogical, digital, affective, regulatory, accommodative, and value-based.